Pedagogical Issues in Integrating Thinking Skills in the Classroom - Noor, Abdullah Mohd (EDUCARE, 2009)
ABSTRACT: The importance of thinking skills in education and in the world of work cannot be denied nowadays. The present issues concerning students not be able to think systematically, less capabilities in active learning, less independent, learning through memorization are issues in this century. Some teachers and parents are worried concerning the situation. What are the views of trainee teachers concerning this matter? What are the hindrances faced by teachers in integrating thinking skills in their classrooms? Is teacher centered methodology to be blamed in not integrating thinking skills in their classroom? What are the relevant teaching strategies that can help in integrating culture of thinking in the classroom? For this study, the methodology in collecting data can be categorized into three phases: exposing trainee teachers with thinking culture in the classroom, using questionnaire to elicit necessary information such as data on traineesâ reactions concerning the research questions, and lastly conducted interviews to consolidate information and data collected through the questionnaire. Results of the study showed that difficulties in integrating thinking skills in the classrooms, thinking skills do not limit to student-centered strategies but also on teacher-centered strategies, and lastly cooperation with many sectors in schools in integrating thinking skills successfully.KEY WORDS: thinking skills, active learning, teaching strategies, and integrating thinking skills successfully.About the Author: Dr. Abdullah Mohd Noor is a Senior Lecturer at the Sultan Hassanal Bolkiah Education Institute UBD (University of Brunei Darussalam), Jalan Tungku Link, Gadong BE 1410, Bandar Seri Begawan, Brunei Darussalam. He can be contacted at: abdullahmohdnoor@yahoo.comHow to cite this article? Noor, Abdullah Mohd. (2009). âPedagogical Issues in Integrating Thinking Skills in the Classroomâ in EDUCARE: International Journal for Educational Studies, Vol.2(1) August, pp.55-68. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 27, 2009); Revised (July 25, 2009); and Published (August 17, 2009).